A study on the status of public libraries in Cavite - Cerrero, Fzaira I. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study was conducted to evaluate the extent of compliance of public libraries in Cavite to the 2015 Standards for Philippine Public Libraries (SPL). Questionnaires were distributed to head librarians and interviews were conducted to supplement the information obtained from the survey. Data gathered from the libraries were then compared against SPL to evaluate their compliance to the current standards. Descriptive method was used to report the current status of the institutions.